Comparison of in-person versus teledermatology consultation in the development of a new score: Analysis of tinea corporis score from baseline up to two follow-up visits - Rosario Andrea; Shankar Shetty Samiksha; Padubidri Kombettu Ashwini; Santhebachalli Gurumurthy Chethana; Garehatty Rudrappa Kanthraj (Wolters Kluwer Medknow Publications, 2023)
Background: Conventionally, dermatophytoses demand at least 6 weeks of treatment. However, frequent follow-up can be a burden for elderly, working population, and COVID-19 pandemic. Teledermatology consultation may reduce follow-up visits. Objective: To propose a new score that provides a periodic clinical audit and minimizes in-person follow-up visits for patient convenience. Materials and Methods: A comparative study between teledermatology and in-person (face-to-face) consultation was conducted in the outpatient department of dermatology JSS Hospital, Mysuru, India from December 2018 to July 2019. The tinea corporis (TC) score constitutes three components: (a) area involvement, (b) erythema intensity, and (c) border visibility. Area involvement by teledermatology consultation was calculated by point counting method of Bahmer. TC score is calculated as the product of area involved and the sum of the erythema intensity and border visibility. These patients were followed up on a weekly basis for a month and values of the proposed score derived from the two methods of consultation were compared. Statistical data collected were tabulated and assessed by the SPSS software version 20 (IBM Corporation, Chicago, USA). Results: There were 150 TC cases. Analysis of 77 patients who completed the first follow-up visit by in-person and teledermatology consultation showed that the tinea corporis score (TCS) decreased from 171.25, 157.94 from baseline to 97.4, 98.61, respectively (P = 0.001). Analysis of 30 patients who completed the second follow-up visits showed a reduction in TCS from 138.2, 152.7 to 68.2, 71.7, respectively (P = 0.001). The Pearson score obtained by the two methods in each visit (0.990, 0.969, and 0.971) resulted in a positive correlation. Conclusion: TC score may be recommended for both in-person and teledermatology consultation. The ease of calculation, objective assessment, and application of TC score in teledermatology consultation are the advantages.